Flora of the projected Mzhanskyi National Nature Park (Kharkiv Region). Part 2: Floodplain complex - Bondarenko, H.M.; Rokytianskyi, A.B. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
Wetlands and floodplains of river valleys are important centres of biodiversity and a source of a large number of different ecosystem services. Due to their resource value, such ecosystems are often subjected to strong anthropic pressure, which leads to the biota decreasing. The importance of the issue of protecting natural environments in the Kharkiv region is very valuable, because the percentage of protected areas in the region is one of the smallest among other administrative regions of Ukraine. At the same time, the representation of wetlands and floodplains in the network of nature reserves of the region is insignificant, which emphasises the need to preserve the most valuable and typical areas. One of such perspective objects is the projected Mzhanskyi National Nature Park, which combines pinewood and floodplain complexes in the middle reaches of the Mozh River. A detailed analysis of the flora of the pine complexes of the designed park is presented in the first part of the article, while this part is devoted to the analysis of the floodplain complexes' flora of the planned nature conservation object. According to the results of field and retrospective research, it was established that the flora of the floodplain part of the park consists of at least 457 species, subspecies and hybrids of vascular plants. Their full list with the annotation is presented in the article. The systematic structure of the flora is typical and corresponds to other local floras of the Kharkiv Region. Among the families, the following are most represented: Asteraceae (61 species – 13.4 %), Poaceae (42 species – 9.2 %), Fabaceae (24 species – 5.3 %), Cyperaceae (23 species – 5.0 %), Lamiaceae (22 species – 4.8 %), Plantaginaceae s.l. and Ranunculaceae (18 species – 3.9 % each), Brassicaceae and Rosaceae (15 species – 3.3 % each). The results of the fractional analysis of the flora indicate that the plant cover is exposed to strong anthropic pressure (IS = 49.8 %). Nevertheless, the transformation of the flora occurs mainly due to autochthonous synanthropic species. The fraction of alien species is 18.4 %, which is less than similar values in other studied territories. Among the alien species, representatives of the North American and Mediterranean flora prevail. Among the adventitious species, Elodea canadensis and Vallisneria spiralis provide a high phytosociological activity in the studied area. However, we found localities of 34 rare species protected at different levels. Among them, 9 are included in the Red Book of Ukraine (Anacamptis palustris, Dactylorhiza fuchsii, D. incarnata, D. majalis, Epipactis palustris, Gladiolus tenuis, Stipa borysthenica, Tragopogon donetzicus, and Utricularia × neglecta), 2 are included in Resolution 6 of the Bern Convention (Ostericum palustre and Salvinia natans), and 23 species are regionally rare in the Kharkiv Region (Cicuta virosa, Inula helenium, Parnassia palustris, Ranunculus lingua, Stratiotes aloides, etc.). Also, during the field surveys, several species rare for the region that do not have an actual protected status were discovered (Carex rostrata, Cirsium esculentum, Gratiola officinalis, Hippuris vulgaris, Klasea lycopifolia, Limonium alutaceum, Ranunculus flammula, R. kauffmanii, R. polyphyllus, Scrophularia oblongifolia, etc.). The growth of a new species of Veronica catenate for the Kharkiv region has been confirmed.